Water the Rocks Make - McElroy, David (Book collections on Project MUSE., 2022)
"The poems of Water the Rocks Make commit into words the turbulence of emotion and thought stirred up by life's events: family trauma, psychiatric instability, the legal system, the death of a loved one, identity, cultural displacement, work, loss, creativity, and through everything, love.-Provided by the Publisher"--